The Upper Triassic alkaline magmatism in the NW Iberian Chain (Spain). - Sanz, T.; Lago, M.; Gil, A.; Galé, C.; Ramajo, J.; Ubide, T.; Pocoví, A.; Tierz, P.; Larrea, P. (Journal of Iberian Geology, 2013)
We have carried out a complete study of the Upper-Triassic alkaline magmatism on the northwestern margin of the Iberian Chain. This magmatism is composed of mafic sills, which intrude the Keuper facies in two geographic sectors: the Cameros Massif (NW) and the Moncayo Massif (SE). In both of these sectors, the rocks are characterised by an intense alteration (spilitisation). The field relationships point to an Upper Triassic age for the studied sills, given that: 1) interactions are recognised between the magma and wet, unconsolidated host sediments, suggesting that the magma was emplaced during or shortly after the deposition of the Keuper facies; 2) in the Moncayo sector a conglomerate bed that includes igneous clasts overlaies the sills and passes upwards to the Norian-Rhaetian Imón Fm. According to the petrological and geochemical features of the sills, an internal differentiation can be recognised inwards, with the developments of three zones: chilled margins, central facies and pegmatoid facies. The rocks are porphyritic and are mainly composed of phenocrysts of pseudomorphed olivine and microcrysts of plagioclase, opaque minerals and minor clinopyroxene. Vesicles and xenoliths of the host sedimentary rocks are also recognised, especially at the chilled margins. The mineral assemblage is constant across the sills but the mineral proportions vary among the different zones. The sills are basic to intermediate rocks. They are classified as basalts to dacites with an alkaline geochemical affinity. According to the trace element contents, this magmatism is related to an enriched sub-lithospheric mantle source affected by crustal contamination. Considering the Upper Triassic magmatisms from southwestern Europe, two types can be distinguished. On the one hand, the magmatisms in the Catalonian Coastal Ranges and SE France are paleogeographically located in the inner platform and are related to deep, astenospheric mantle sources with no evidence of crustal contamination. On the other hand, the magmatisms in the NW Iberian Chain –this study-, the External Betics and the Brescian Prealps are situated in a more litoral position and are related to a shallower, lithospheric mantle with evidence of crustal contamination. These differences could be related to the thickness of the continental crust, which might be thinner in the inner areas of the platform.